2014
DOI: 10.1016/j.visres.2014.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Modeling trial by trial and block feedback in perceptual learning

Abstract: Feedback has been shown to play a complex role in visual perceptual learning. It is necessary for performance improvement in some conditions while not others. Different forms of feedback, such as trial-by-trial feedback or block feedback, may both facilitate learning, but with different mechanisms. False feedback can abolish learning. We account for all these results with the Augmented Hebbian Reweight Model (AHRM). Specifically, three major factors in the model advance performance improvement: the external tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 35 publications
2
36
0
Order By: Relevance
“…The Augmented Hebbian Reweighting Model (AHRM) accounts for several perceptual learning phenomena, including transfer across features and locations (Dosher et al, 2013; Liu, Dosher & Lu, 2014; Petrov, Dosher & Lu, 2005, 2006). Interestingly, model simulations for orientation training of Gabor stimuli suggested that learning increases the weight not only for the most diagnostic orientation channels but also for the target spatial-frequency bands (Petrov, Dosher & Lu, 2005, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The Augmented Hebbian Reweighting Model (AHRM) accounts for several perceptual learning phenomena, including transfer across features and locations (Dosher et al, 2013; Liu, Dosher & Lu, 2014; Petrov, Dosher & Lu, 2005, 2006). Interestingly, model simulations for orientation training of Gabor stimuli suggested that learning increases the weight not only for the most diagnostic orientation channels but also for the target spatial-frequency bands (Petrov, Dosher & Lu, 2005, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…One possible reason for this lack of consensus is that feedback has largely been treated in a unitary fashion in most studies of perceptual learning. Specifically, traditional experimental procedures used to examine perceptual learning have relied on binary judgments, and have thus been restricted to manipulating feedback in a purely success-based fashion (see Liu, Dosher, & Lu, 2014 for model and review). By contrast, there is a long history of examining more graded forms of feedback in motor learning (Salmoni, Schmidt, & Walter, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…In this modeling study Liu, Dosher, and Lu (2014) extended their reweight model to account for the complex effects of feedback on perceptual learning (Herzog & Fahle, 1999; Liu, Lu, & Dosher, 2010; Seitz et al, 2006). They incorporated three major factors that facilitate perceptual learning: the external trial-by-trial feedback, the self-generated output as an internal feedback when no external feedback is available, and the adaptive criterion control based on the block feedback.…”
Section: Articles In This Special Issuementioning
confidence: 99%